Qualitative Impact of Strategic Planning on Performance of Rural and Community Banks in Ghana (Global Journal of Management and Business Research, 2018)
Companies big and small commit a lot of resources both material and financial in planning. Little or nothing is done to assess the impact of the planning and the planning process. The question that arises is #x2018;does it pay to commit such resources and time in planning and does planning process impact on the performance of financial institutions apart from the financial indicators? This study explores the qualitative implications of strategic planning and the planning process .It assesses strategic planning impacts from behavioral perspectives as against purely profit or what appears on the financial statements of financial institutions in Ghana. Qualitative data were collected from primary and secondary sources. Data was collected from primary and secondary sources .Board of Directors, Staff and customers of the bank were interviewed through questionnaire administration and open-ended discussions. The theory section looks at strategic planning, strategic planning process, impact of strategic planning and strategic management. The findings indicated that there is enough justification for financial institutions including rural and community banks to commit the required resources in planning. It can result in improved understanding of the organization#x2019;s objectives and overall direction. It can facilitate implementation of organizational objectives and goals. They agreed and accepted the impacts and resolved to continuously plan to maximize these impacts.
Keywords: rural and community banks; strategic planning; assessing; ghana; qualitative impact